Increased pro-SFTPB in HDL promotes the pro-inflammatory transition of HDL and represents a sign of poor prognosis in ARDS patients - Liu Yang; Zhuo Xu; Zhenyan Wang; Fangping Ding; Zhipeng Wu; Xiaoqian Shi; Jing Wang; Yingmin Ma; Jiawei Jin (Journal of Translational Medicine)
Abstract Background Acute respiratory distress syndrome (ARDS) is causatively associated with excessive alveolar inflammation involving deregulated pro-inflammatory macrophage polarization. High-density lipoprotein (HDL) showed critical anti-inflammatory roles by modulating macrophage function, and its adverse transition to pro-inflammation has an important role in the pathogenesis of ARDS. However, the relationship between HDL protein constituents and functional remodeling is unknown in ARDS. Methods Proteomic techniques were applied to examine the protein profile changes in HDL from septic-ARDS patients versus HDL from healthy controls across two distinct cohorts: a discovery cohort (8 patients and 8 healthy controls) and a validation cohort (22 patients and 10 healthy controls). The changed components significantly associated with prognosis were identified. Luminex assessed the levels of 38 plasma cytokines and chemokines. The in vitro constructed pro-SFTPB enriched HDL was applied to confirm the effect on M1 polarization of THP1-derived macrophage. Results 18 proteins were validated from 102 changed HDL proteins identified in the discovery cohort, including HDL particle components, such as apolipoproteins, pro-inflammatory substances known as serum amyloid As (SAAs), and anti-oxidative proteins like paraoxonases (PONs). Among these proteins, only the increase of pro-SFTPB in HDL was significantly associated with poor prognosis of ARDS patients. Notably, HDL-pro-SFTPB level was correlated with plasma pro-inflammatory cytokines and chemokines levels. The correlation assay of pro-SFTPB with other HDL components showed that it was positively and negatively correlated with SAA2 and PON3, respectively. Furthermore, the in vitro studies confirmed that the pro-SFTPB enriched HDL significantly promoted M1 polarization of monocyte-derived macrophages. Conclusions The increase of HDL-pro-SFTPB promotes HDL pro-inflammatory transition during septic ARDS, leading to exacerbated progression of ARDS through enhancing M1 macrophage polarization. HDL-pro-SFTPB could be a useful prognostic biomarker for septic ARDS.